MEDULLOBLASTOMA INCIDENCE AND SURVIVAL - A POPULATION BASED STUDY. (3rd October 2018) - Khan, Maria; Wong, Kwok; Jardel, Dem; Broggio, John; Stiller, Charles; McCabe, Martin
Abstract: Medulloblastoma can occur at any age, but is most frequent in infancy and childhood. There have been no previous detailed reports of incidence or survival across all age groups in the UK and few population-based reports internationally. This project provides for the first time population-based data on medulloblastoma incidence and survival across all ages in England. METHOD: We extracted data for all patients with medulloblastoma diagnosed during 2001–2015, in England, from the English national cancer registry. The crude incidence rates per 100, 000 were calculated, for all individuals and subdivided by age and 3/5yr periods. We also calculated 1-, 3-, 5- and 10-yr Kaplan Meier survival by 5-yr periods, for the overall cohort and by age group. RESULTS: The overall average crude incidence rate was 0.12 per 100, 000 (2001–2015), with no significant trend between 5-yr periods. However, the incidence rate for the age groups 0–3 and 4–14 was significantly higher than the older age groups. Male incidence was significantly higher than female. The 1-, 3-, and 5-yr (2001–2005) survival was significantly lower for infants than for older children. There was no significant difference in survival between children and the Teenage/Young Adult (TYA) group, for 5-yr and 10-yr survival. For all age groups, 10-yr survival was lower than 5-yr. All age 1-yr survival improved in the most recent period (2011–2015), 87.2% compared to 84.9% in 2006–2010. Individuals aged 4–14 and 15–24 had the highest 1-yr survival (2006–2010), 90.1% and 92.3% respectively, 5-yr (2006–2010), 64.0% and 76.9%, 10-yr (2001–2005), 65.4% and 63.6% respectively. CONCLUSION: Medulloblastoma survival continues to decrease beyond 5-yr post diagnosis and varies by age group. Future investigation of whether variation in survival by age is related to systematic differences in tumour biology or in treatment could indicate ways of improving outcome for poorer-prognosis age groups.